Five days in Paris : a novel - Steel, Danielle (Delacorte Press, 1995)
The romance of two Americans in Paris, both staying at the Ritz hotel. He is Peter Haskell, 44, a pharmaceutical executive working on a cancer cure who is the father of three sons. She is Olivia Thatcher, 34, wife of a U.S. senator with presidential ambitions, and she is grieving for her son, dead from cancer.